The Effect of Physical Exercise on Cognitive Impairment in Patients with Diabetes Mellitus - Yeane Anastania; Debie Dahlia; Sri Yona; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2025)
Diabetes mellitus has been proven to be associated with cognitive decline and an increased risk of dementia. Exercise, both physical activity and brain training, as a non-pharmacological intervention, has the potential to improve cognitive function. Objective to investigate the effect of physical activity on cognitive impairment in patients with diabetes mellitus. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method was used to select articles. The JBI critical appraisal checklist was used for quality assessment. Articles were searched through PubMed, Medline, and ScienceDirect databases from 2014 to 2024, using full-text articles. Out of 507 articles identified, 13 articles were included in the review, selected through a screening process based on predefined inclusion and exclusion criteria, and all demonstrated that physical activity, cognitive training, combined training, and training with lifestyle modifications can improve cognitive function in patients with type 2 diabetes mellitus. Exercise programs such as aerobic exercise, combined training, or other more specific exercises have been proven to improve cognitive function and metabolic indicators in patients with diabetes mellitus, such as HbA1c levels and insulin resistance. However, the majority of study participants were older adults.